Evidence‐based clinical practice guidelines for liver cirrhosis 2020 - Yoshiji, Hitoshi; Nagoshi, Sumiko; Akahane, Takemi; Asaoka, Yoshinari; Ueno, Yoshiyuki; Ogawa, Koji; Kawaguchi, Takumi; Kurosaki, Masayuki; Sakaida, Isao; Shimizu, Masahito; Taniai, Makiko; Terai, Shuji; et al. (Hepatology research, 2021)
The first edition of the clinical practice guidelines for liver cirrhosis was published in 2010, and the second edition was published in 2015 by the Japanese Society of Gastroenterology (JSGE). The revised third edition was recently published in 2020. This version has become a joint guideline by the JSGE and the Japanese Society of Hepatology (JSH). In addition to the clinical questions (CQs), background questions (BQs) are new items for basic clinical knowledge, and future research questions (FRQs) are newly added clinically important items. Concerning the clinical treatment of liver cirrhosis, new findings have been reported over the past 5 years since the second edition. In this revision, we decided to match the international standards as much as possible by referring to the latest international guidelines. Newly developed agents for various complications have also made great progress. In comparison with the latest global guidelines, such as the European Association for the Study of the Liver (EASL) and American Association for the Study of Liver Diseases (AASLD), we are introducing data based on the evidence for clinical practice in Japan. The flowchart for nutrition therapy was reviewed to be useful for daily medical care by referring to overseas guidelines. We also explain several clinically important items that have recently received focus and were not mentioned in the last editions. This digest version describes the issues related to the management of liver cirrhosis and several complications in clinical practice. The content begins with a diagnostic algorithm, the revised flowchart for nutritional therapy, and refracted ascites, which are of great importance to patients with cirrhosis. In addition to the updated antiviral therapy for hepatitis B and C liver cirrhosis, the latest treatments for non‐viral cirrhosis, such as alcoholic steatohepatitis/non‐alcoholic steatohepatitis (ASH/NASH) and autoimmune‐related cirrhosis, are also described. It also covers the latest evidence regarding the diagnosis and treatment of liver cirrhosis complications, namely gastrointestinal bleeding, ascites, hepatorenal syndrome and acute kidney injury, hepatic encephalopathy, portal thrombus, sarcopenia, muscle cramp, thrombocytopenia, pruritus, hepatopulmonary syndrome, portopulmonary hypertension, and vitamin D deficiency, including BQ, CQ and FRQ. Finally, this guideline covers prognosis prediction and liver transplantation, especially focusing on several new findings since the last version. Since this revision is a joint guideline by both societies, the same content is published simultaneously in the official English journal of JSGE and JSH.